PENGARUH LINGKUNGAN KERJA TERHADAP LOYALITAS KARYAWAN MELALUI MOTIVASI KERJA DI SHERATON BALI KUTA RESORT - Ni Kadek Anjeli; Heryanda, Komang Krisna (Jurnal Manajemen Perhotelan dan Pariwisata, 2025)
This study uses quantitative research that aims to determine the effect of the work environment on employee loyalty through work motivation at Sheraton Bali Kuta Resort. The population in this study amounted to 43 people from all employees in the Front Office department at Sheraton Bali Kuta Resort. The sample taken for this study used nonprobability sampling with saturated sampling techniques. The data collection technique used was a questionnaire measured using a Likert scale. The data analysis technique used path analysis with the help of the Statistical Package for The Social Science (SPSS) version 25 program. The results of the study indicate that (1) The work environment has a positive and significant effect on employee work motivation at Sheraton Bali Kuta Resort, (2) The work environment has a positive and significant effect on employee loyalty at Sheraton Bali Kuta Resort, (3) Work motivation has a positive and significant effect on employee loyalty at Sheraton Bali Kuta Resort, and (4) The work environment has a significant effect on employee loyalty through work motivation or work motivation mediates the effect of the work environment on employee loyalty.